MORE THEN A TRIAD: UNDERSTANDING THE COMPLEXITY OF PRUNE BELLY SYNDROME - Anita Krowiak; Karolina Krowiak; Anita Warzocha; Piotr Pitrus; Karol Bednarz; Maria Jasiewicz; Gabriela Majka; Magdalena Kowalczyk; Wiktoria Hander; Aleksandra Karnaś (International Journal of Innovative Technologies in Social Science, 2025)
Aims: Prune Belly Syndrome (PBS), also known as Eagle-Barrett syndrome, is a rare congenital disorder defined by a triad of abdominal muscle deficiency, urinary tract anomalies and bilateral cryptorchidism. This review aims to summarize current knowledge on its etiology, clinical presentation and management. Methodology: This review was based on an extensive search of literature related to PBS using PubMed, Google Scholar and other scientific databases. Relevant clinical studies, reviews and case reports were analyzed to summarize current knowledge on diagnosis, management and outcomes of PBS. State of knowledge: PBS affects approximately 1 in 30,000 to 1 in 50,000 live births, with a strong male predominance. Its pathogenesis is thought to be multifactorial, involving mesodermal maldevelopment and possible genetic factors. The clinical spectrum ranges from severe cases with renal dysplasia and pulmonary hypoplasia to a milder, incomplete form. Woodard’s classification is commonly used to guide prognosis and treatment. Besides the classic triad, patients may present with gastrointestinal, musculoskeletal, cardiopulmonary and developmental systems. Early prenatal diagnosis is possible through imaging. Postnatal care includes urologic reconstruction, orchiopexy, abdominoplasty, renal support and in some cases, transplantation. Assisted reproductive techniques have allowed for fertility in select male patients. Conclusion: PBS is a complex and variable condition requiring early diagnosis and individualized, multidisciplinary care. Advances in surgical and medical treatment have improved outcomes, but long-term monitoring and supportive care remain essential for preserving function and quality of life.